COMPARISON BETWEEN HEMODYNAMIC CHANGES OF ATRACURIUM AND CISATRACURIUM IN PATIENTS UNDERGOING CABG SURGERY - Muhammad Ali (Army Medical College Rawalpindi, 2020)
Objective: To compare the hemodynamic effects of Atracurium versus Cisatracurium in Cardiac Patients Undergoing coronary artery bypass graft Surgery.